ANALISIS PERAN MUSYRIFAH SEBAGAI PEMBIMBING ASRAMA DALAM PEMBENTUKAN ADAB DAN KEMANDIRIAN SANTRIWATI DI SALAFIYAH WUSTHA ICBB YOGYAKARTA - Umareni Umareni; Najla Aulia Kholaidah; Qoriina Qoriina; Widyaningtyas Kusuma Wardani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The cultivation of manners and independence is a fundamental aspect of character education in Islamic boarding schools, especially for female students in their teenage years who are developing their personal identity. Within the dormitory setting, musyrifahs play a strategic role as mentors, guides, supervisors, and role models in shaping the students’ behavior and daily discipline. This study aims to analyze the role of musyrifah as dormitory mentors in fostering manners and independence among female students at Pondok Pesantren Salafiyah Wustha Islamic Centre Bin Baz Putri Yogyakarta. Using a qualitative approach with a case study design, this research explores daily interactions, dormitory regulations, and religious values that contribute to character formation. Data were collected through in-depth interviews and documentation, then analyzed using Miles and Huberman’s interactive analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that musyrifahs play three main roles: as uswatun hasanah (exemplary figures), as mentors in instilling manners and worship practices, and as supervisors ensuring daily discipline. Manners are developed through habituation, modeling, and direct advice, while independence is built through personal responsibility, collective activities, and a tiered supervision system. Supporting factors include the pesantren’s Salafi-based culture, emotional closeness between musyrifah and students, and a structured evaluation system of manners.